Enabling self-directed computer use for individuals with cerebral palsy: a systematic review of assistive devices and technologies. - Davies TC; Mudge S; Ameratunga S; Stott NS (Developmental Medicine & Child Neurology, 2010)
AIM: The purpose of this study was to systematically review published evidence on the development, use, and effectiveness of devices and technologies that enable or enhance self-directed computer access by individuals with cerebral palsy (CP). METHODS: Nine electronic databases were searched using keywords 'computer', 'software', 'spastic', 'athetoid', and 'cerebral palsy'; the reference lists of articles thus identified were also searched. Thirty articles were selected for review, with 23 reports of development and usability testing of devices and seven evaluations of algorithms to increase computer recognition of input and cursor movements. RESULTS: Twenty-four studies had fewer than 10 participants with CP, with a wide age range of 5 to 77 years. Computer task performance was usually tested, but only three groups sought participant feedback on ease and comfort of use. International standards exist to evaluate effectiveness of non-keyboard devices, but only one group undertook this testing. None of the study designs were higher than American Academy for Cerebral Palsy and Developmental Medicine level IV. INTERPRETATION: Access solutions for individuals with CP are in the early stages of development. Future work should include assessment of end-user comfort, effort, and performance as well as design features. Engaging users and therapists when designing and evaluating technologies to enhance computer access may increase acceptance and improve performance.